2022
DOI: 10.4102/td.v18i1.1256
|View full text |Cite
|
Sign up to set email alerts
|

Securing the cybersafety of South African online high school learners beyond COVID-19

Abstract: The unprecedented online learning that took place at several schools during the coronavirus disease 2019 (COVID-19) pandemic is predicted to continue on the same trajectory when learners return to classroom learning. Continuing with online learning implies that learners will spend most of their time learning and socialising online, which exposes them to cybersecurity risks. Hence, this study investigated strategies for securing the cybersafety of online learners at South African high schools. The study adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…South African schools were encouraged to take up online teaching and learning only with the arrival of the COVID-19 pandemic (Maree, 2022). Some challenges identified as affecting this transition were cyber safety issues, unreliable network connectivity, limited coverage in rural areas, and expensive bandwidth (Chipangura & Dtendjo-Ndjindja, 2022;Mukuna & Aloka, 2020). Mukuna and Aloka (2020) found that online teaching and learning in rural areas was mainly constrained by poor connectivity to the internet network, slow connections, and broadband costs.…”
Section: Internet Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…South African schools were encouraged to take up online teaching and learning only with the arrival of the COVID-19 pandemic (Maree, 2022). Some challenges identified as affecting this transition were cyber safety issues, unreliable network connectivity, limited coverage in rural areas, and expensive bandwidth (Chipangura & Dtendjo-Ndjindja, 2022;Mukuna & Aloka, 2020). Mukuna and Aloka (2020) found that online teaching and learning in rural areas was mainly constrained by poor connectivity to the internet network, slow connections, and broadband costs.…”
Section: Internet Connectivitymentioning
confidence: 99%
“…To meet their obligations, teachers required a variety of online teaching tools (König et al, 2020). Teachers needed, inter alia, subject-specific online tools (Mishra & Koehler, 2006); online tools to manage classrooms; and online tools to ensure that students were disciplined, ethical, and cyber-protected (Chipangura & Dtendjo-Ndjindja, 2022). When schools provided numerous new tools in a short period of time, the situation became highly complex for teachers.…”
Section: Core Literature Review F Indingsmentioning
confidence: 99%